Apocalyptic Phenomenology: The Culmination of the Phenomenological Movement - Balázs M. Mezei (Religions, 2022)
In this article, I delineate a notion of phenomenology, which differs in many ways from earlier approaches. I term this understanding apocalyptic in the sense that this phenomenology discloses not only the essences of particular things, logical entities, ideas, and transcendental processes, but beyond them, it reveals reality in its essential openness to newness. The term apocalupsis refers not simply to the unveiling of something unknown earlier, but more importantly to the central determinant of reality in that it discloses irreducible newness. I show that the phenomenon of self-disclosure or revelation was at the center of the work of the first phenomenologists, such as Franz Brentano and Edmund Husserl; I emphasize the notion of phenomenological revelation in the thought of Max Scheler and Martin Heidegger. In this context, I offer an interpretation of the phenomenologies of Emmanuel Lévinas, Michel Henry, and Jean-Luc Marion. I argue that the notion of nouveauté novatrice of Miklos Vetö is a phenomenologically inspired insight into the nature of the essence of phenomenology. I claim that newness is the core of reality engendering a new conception of phenomenology as a philosophy of reality–a phenomenology aptly termed neology, a development of what is known as “the phenomenological movement”.